2019
DOI: 10.18203/2349-3933.ijam20192254
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones, blood glucose and glycosylated hemoglobin in healthy Sudanese subjects

Abstract: Background: Diabetes mellitus and thyroid diseases are the most prevalent metabolic disorders in Sudan. The value of HbA1C reflects the glycemic status over the last 2-3 months. So, in this study, an insight for thyroid hormone regulation of glucose metabolism is investigated. Is to study the association between thyroid hormones levels, fasting blood sugar (FBS) and HbA1c in healthy adults.Methods: A cross sectional study was performed in a healthy Sudanese cohort in the period between September 2017 to Novemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Similar results were reported by Kumar and co-workers (24), who found that the mean total cholesterol and LDL levels were elevated in hypothyroidism patients compared to controls. Thyroid dysfunction is highly common in patients with a longer duration of diabetes, and poor glycemic control and is associated with substantially higher serum cholesterol and triglyceride levels (25). The result of correlation showed that there was a significant association between Glucose and Arginase.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were reported by Kumar and co-workers (24), who found that the mean total cholesterol and LDL levels were elevated in hypothyroidism patients compared to controls. Thyroid dysfunction is highly common in patients with a longer duration of diabetes, and poor glycemic control and is associated with substantially higher serum cholesterol and triglyceride levels (25). The result of correlation showed that there was a significant association between Glucose and Arginase.…”
Section: Resultsmentioning
confidence: 99%
“…18 A Similar results were observed in the study conducted by Raghuwansh K et al 14 The study shows a affirmative co-relation between HbA 1 C and TSH and it was highly statistically significant and negative correlation between HbA 1 C and T 3 which was statistically significant and positive correlation between HbA 1 C and T 4 and was statistically non significant. Altered glucose homeostasis with reduced absorption and decreased utilization of glucose are related with hyper insulinemia and insulin resistance probably causing transient elevations in the glucose concentrations consequently contributing to glycation of serum proteinwhich was observed by Asmabi et al and Tarig et al 17,19…”
mentioning
confidence: 94%